Treatment of mine water containing ammonia nitrogen by sodium hexametaphosphate modified zeolite - Liping ZHANG; Xiang HU; Weiwei WANG; Wenbo LEI; Huitong LI; Huaran SUN; Yongqi ZHAN; Zeyu LIAN (Meitan kexue jishu)
The ammonium nitrogen (NH4+—N) exceeding standard in mine waters is a widespread issue in certain mining regions of our country. As the demand for its removal escalates, a strategy involving the modification of natural zeolite (NZ) with sodium hexametaphosphate (SHMP) immersion was employed to enhance its removal efficiency. The results demonstrated that after 3 h of immersion in a 0.1 mol/L SHMP solution, SHMP-modified zeolite (SHMP−NZ) was prepared. Under conditions with an initial NH4+—N concentration of 5 mg/L and a dosage of 2 g/L, an oscillatory adsorption of 2 h led to a NH4+—N removal efficiency of 95.7%, representing a 39.9% enhancement compared to the unmodified natural zeolite. Scanning electron microscopy and surface area measurements revealed that upon modification, the zeolite exhibited enlarged pores, a smoother and more loosely structured surface, increased specific surface area, decreased micropore volume, and an augmentation in mesopore, macropore, and average pore diameter. Analyses using X-ray diffraction and Fourier-transform infrared spectroscopy indicated no significant alteration in the fundamental framework of the modified zeolite. The adsorption of NH4+—N by SHMP−NZ was optimal under weakly acidic or neutral conditions. The impact of coexisting cations on the adsorption followed the order K+ > Na+ > Ca2+ > Mg2+. Pseudo-first-order, pseudo-second-order, and Elovich kinetic nonlinear fitting suggested that both natural zeolite and SHMP−NZ adsorption of NH4+—N is better aligned with the pseudo-second-order kinetic model. The adsorption process was identified as chemisorption (ion exchange), and particle inner diffusion models revealed that the NH4+—N adsorption by both materials involves three stages: external diffusion, internal diffusion, and reaction equilibrium. The Freundlich isotherm model revealed that SHMP−NZ is more conducive to NH4+—N adsorption compared to NZ. The Langmuir isotherm model aptly described the NH4+—N adsorption process by both natural zeolite and SHMP−NZ, with correlation coefficients R2 being 0.9636 and 0.9828, respectively. The maximum NH4+—N adsorption capacity of SHMP−NZ was 11.03 mg/g, an 88.23% improvement compared to NZ. Adsorption thermodynamics showed that the Gibbs free energy (ΔG) values at each test temperature were less than 0, while the enthalpy change (ΔH) and entropy change (ΔS) were greater than 0. This indicates that the adsorption process is constituting an entropy-increasing reaction which is favorable for the removal of NH4+—N. After five regenerations, SHMP−NZ still maintains an ammonia nitrogen removal efficiency of 89.7%. Research on treating low-concentration ammonia nitrogen in actual mine water with SHMP−NZ shows that after 1 h of oscillating adsorption at a dosage of 1 g/L and at 25 °C, the effluent meets the ammonia nitrogen requirements of category III as per the environmental quality standards for surface water.